Cave adaptation favors aging resilience in the Mexican tetra - Ansa E. Cobham; Alexander Kenzior; Pedro Morales-Sosa; Jose Emmanuel Javier; Selene Swanson; Christopher Wood; Nicolas Rohner (npj Metabolic Health and Disease)
Abstract All animals age, but the rate of aging across species varies widely. The environmental pressures and molecular factors underlying this remarkable diversity in aging across species remains largely enigmatic. The Mexican tetra, Astyanax mexicanus, provides an intriguing new model to study how adaptation to different environments alter aging. This species exists as the river-dwelling surface fish, living in food and light rich environments, and the blind cave-adapted cavefish, thriving in dark, nutrient-limited, caves. How adaption to these extreme environments alter aging in this species remains unknown. Here, we compared aging markers between surface and cavefish populations, focusing on morphological, behavioral changes, and molecular signatures. We found aging markers were more pronounced in surface fish, but less distinct in aged cavefish. We also observed that insulin receptor mutation is limited in its impact to increase lifespan in cavefish. Instead, metabolic shifts, particularly in mitochondrial function, may contribute to cavefish’s extended longevity.